Impact Analysis of Internet of Things Implementation on Supply Chain Efficiency - Susmanto, Dede; Gea, Mira Astuti; Saputro, Aditya Hendri (Journal Collabits, 2024)
Technology known as the Internet of Things (IoT) has brought about significant changes in many aspects of daily life, including pet care. This research aims to analyze the impact of IoT device efficiency on patient outcomes. Efficiency benchmarks are essential for businesses to meet increasingly challenging global market conditions. It is anticipated that by utilizing IoT capabilities for real-time data collection, processing, and analysis, visibility, coordination, and process optimization will increase in pass parity.